Validation of a Photoplethysmographic Heart Rate Monitor: Polar OH1 - Hermand, Eric; Cassirame, Johan; Ennequin, Gaël; Hue, Olivier (International Journal of Sports Medicine, 2019)
This study assessed the validity of a photoplethysmographic heart rate (HR) monitor, the Polar OH1 in various sports performed in ecological conditions: running, cycling, soccer, kayaking, walking, tennis and fitness. Seventy trained athletes (56 males, 14 females) wore the Polar OH1 armband and the H7 chest belt during training. A total of 390 h and 38 min of recording were compared using a 20-bpm window to assess data quality, and Bland-Altman agreements and ICC analyses were used to test accuracy. Linear regression analyses evaluated the HR accuracy and correlation with skin tone. Training loads (TRIMPs) were compared for each session. Reliability was high for endurance sports (>99%) and lower for sports involving arm movements (92~95%). Biases were slightly negative for all sports, whereas widths of limits of agreement varied from 7–20bpm. Bland-Altman agreements were all under 5% except tennis, kayak and fitness. HR accuracy was positively correlated to skin tone (p<0.05). Finally, TRIMPs from the OH1 device were inferior to criterion’s (except walking and soccer), within a 3% range from reference. Hence, OH1 represents a valid tool to monitor instantaneous HR and training load, especially for endurance sports.
Keywords: photoplethysmography; accuracy; exercise; Bland-Altman; training load; skin type